Effect of involvedAspergillusspecies on galactomannan in bronchoalveolar lavage of patients with invasive aspergillosis. Issue 7 (July 2017) - Taghizadeh‐Armaki, Mojtaba; Hedayati, Mohammad T.; Moqarabzadeh, Vahid; Ansari, Saham; Omran, Saeed Mahdavi; Zarrinfar, Hossein; Saber, Sasan; Verweij, Paul E.; Denning, David W.; Seyedmousavi, Seyedmojtaba
Abstract : Purpose. : The detection of galactomannan (GM) in bronchoalveolar lavage (BAL) fluid is an important surrogate marker for the early diagnosis and therapeutic monitoring of invasive aspergillosis (IA), regardless of the involved species of Aspergillus . Here, we utilized the Platelia Aspergillus GM enzyme immunoassay (Bio‐Rad) to evaluate the GM index in BAL fluid samples from patients with proven, probable or putative IA due to Aspergillusflavus versus Aspergillusfumigatus. Methodology. : In a prospective study between 2009 and 2015, 116 BAL samples were collected from suspected IA patients referred to two university hospitals in Tehran, Iran. Key findings. : According to European Organization for Research and Treatment of Cancer and Mycoses Study Group and Blot criteria, 35 patients were classified as IA patients, of which 33 cases tested positive for GM above 0.5 and, among these patients, 22 had a GM index ≥1. Twenty‐eight were culture positive for A. flavus and seven for A. fumigatus . The GM index for A. flavus cases was between 0.5‐6.5 and those of A. fumigatus ranged from 1 to 6.5. The sensitivity and specificity of a GM index ≥0.5 in cases with A. flavus were 86 and 88% and for A. fumigatus patients were 100 and 73%, respectively. Conclusion. : Overall, the mean GM index in patients with A. fumigatus (3.1) was significantly higher than those of A. flavus (1.6; P ‐value=0.031) and the sensitivity of GM lower for A. flavus when compared to A. fumigatus. This finding has implications for diagnosis in hospitals and countries with a high proportion of A. flavus infections.